Integration of transcriptome and proteome analyses reveal molecular mechanisms for formation of replant disease in Nelumbo nucifera. Issue 57 (20th September 2018) - Dong, Chen; Wang, Ran; Zheng, Xingfei; Zheng, Xingwen; Jin, Lifeng; Wang, Hongjiao; Chen, Shuang; Shi, Yannan; Wang, Mengqi; Liu, Die; Yang, Yanhui; Hu, Zhongli
Abstract : Complementary transcriptomic and proteomic analyses unveiled the mechanism of replant disease in Nelumbo nucifera, a widely planted aquatic crop in Asia. Abstract : The normal growth of Nelumbo nucifera, a widely planted aquatic crop in Asia, was severely ruined by replant disease. The mechanism of replant disease was still unknown in aquatic crops. Complementary transcriptomic and proteomic analyses were performed by comparing seedings of first-year planting (FP) and consecutive planting (CP). 9810 differentially expressed genes (DEGs) were identified between FP and CP. Additionally, 975 differentially expressed proteins (DEPs) were obtained. The correlation of proteome and transcriptome illustrated phenylpropanoid biosynthesis, flavonoid biosynthesis, metabolic pathways, and MAPK signaling pathways were significantly activated. Peroxidase, determined as one of the key proteins in replant disease of N. nucifera, was phylogenetically analyzed. A new depiction of the molecular mechanism causing replant disease in N. nucifera was illustrated. A consecutive monoculture stimulated the generation of reactive oxygen species (ROS) and ethylene, altered the metabolic balance of lignin and flavonoid, and attenuated the activity of antioxidant enzymes through DNA methylation. Therefore, the accumulation of autotoxic allelochemicals and the deficiency of antioxidant enzymes unavoidably suppressed the normal growth and development of replanted N. nucifera .